2018
DOI: 10.18282/jsd.v3.i2.177
|View full text |Cite
|
Sign up to set email alerts
|

A novel total body digital photography smartphone application designed to detect and monitor skin lesions: a pilot study

Abstract: <p class="Body">Although some smartphone applications are designed for total body photography (TBP), few offer the specificity that enables self- as well as dermatologist-, detection of new lesions, or change in lesion color or in size as little as 1mm, on an ongoing basis. The aim of this study is to assess the sensitivity of a novel TBP application in the detection of changes to color and size of simulated skin lesions. Twenty-five subjects underwent one study visit. After baseline photography, new art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The current CE marking assessment processes are inadequate for protecting the public against the risks created by using smartphone diagnostic or risk stratification apps. Smartphones and dedicated skin cancer apps can have other roles; for example, assisting in skin self-examination, tracking the evolution of suspicious lesions in people more at risk of developing skin cancer,4748 or when used for store and forward teledermatology 4950. However, healthcare professionals who work in primary and secondary care need to be aware of the limitations of algorithm based apps to reliably identify melanomas, and should inform potential smartphone app users about these limitations.…”
Section: Resultsmentioning
confidence: 99%
“…The current CE marking assessment processes are inadequate for protecting the public against the risks created by using smartphone diagnostic or risk stratification apps. Smartphones and dedicated skin cancer apps can have other roles; for example, assisting in skin self-examination, tracking the evolution of suspicious lesions in people more at risk of developing skin cancer,4748 or when used for store and forward teledermatology 4950. However, healthcare professionals who work in primary and secondary care need to be aware of the limitations of algorithm based apps to reliably identify melanomas, and should inform potential smartphone app users about these limitations.…”
Section: Resultsmentioning
confidence: 99%
“…A notable feature of this study was the use of sequential images from patients that were taken as part of an image and nevus biobanking protocol at our institution. This differs from several other studies that used artificial means of generating changes in size and number of cutaneous lesions before analysis, either by drawing them on the skin ( Guido et al., 2018 ) or by digitally modifying the original images to introduce the changes ( Navarro et al., 2019 ). The use of artificial nevi and/or digital changes to nevi may not reflect a real-world situation and may introduce artifacts and/or bias owing to assumptions made when creating or modifying the lesions.…”
Section: Discussionmentioning
confidence: 91%
“…Guido et al previously showed that SkinIO had 92% sensitivity in detecting new or changing lesions. 17 Future studies can explore the role mobile applications may play in remote diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…SkinIO was used as a tool for image collection, with a streamlined interface enabling the physician to quickly browse through organised collections of full body and dermoscopic photos (Figure 2 ). 17 , 18 The application uses a deep neural network‐based outlier detection model that analyzes all photos from a patient's total body photography session, compares each lesion, and highlights lesions most different from the average. The neural network aspect was only used in triage for photography, but not for diagnosis.…”
Section: Methodsmentioning
confidence: 99%